2018
DOI: 10.3892/mmr.2018.8984
|View full text |Cite
|
Sign up to set email alerts
|

COL2A1 mutation (c.3508G>A) leads to avascular necrosis of the femoral head in a Chinese family: A case report

Abstract: Avascular necrosis of the femoral head (ANFH) is a consequence of ischemia. Although the majority of cases of ANFH are sporadic, certain familial cases of ANFH have been reported to be associated with collagen type II α1 chain (COL2A1) mutations, which lead to COL2A1 gene dysfunction. The structure of secreted type II collagen contains a core area with a triple helical glycine (Gly)-X-Y domain, and the replacement of Gly in this region as a result of COL2A1 mutations may damage the structure of type II collage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…However, in 2005, Liu et al identified three families with autosomal dominant inheritance of ANFH and mapped the positions of two related mutations: p.Gly1170Ser occurred in two four‐generation and five‐generation families; and p.Gly717Ser occurred in a three‐generation family . P.Gly1170Ser was subsequently found in two Chinese families in 2014 and 2018 . Moreover, p.Gly582Ser was identified in patients with ANFH …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in 2005, Liu et al identified three families with autosomal dominant inheritance of ANFH and mapped the positions of two related mutations: p.Gly1170Ser occurred in two four‐generation and five‐generation families; and p.Gly717Ser occurred in a three‐generation family . P.Gly1170Ser was subsequently found in two Chinese families in 2014 and 2018 . Moreover, p.Gly582Ser was identified in patients with ANFH …”
Section: Resultsmentioning
confidence: 99%
“…46 P.Gly1170Ser was subsequently found in two Chinese families in 2014 and 2018. 47,95 Moreover, p.Gly582Ser was identified in patients with ANFH. 96 Legg-Calve-Perthes disease (LCPD; MIM #150600) is a form of ANFH in children; its peak incidence occurs between the ages of 4 and 8 years.…”
Section: Types Mainly Involved In Long Bone and Joint Disordersmentioning
confidence: 98%
“…Through Hardy–Weinberg equilibrium test and haplotype analysis, Wang et al found that IGF1 polymorphism was closely related to the susceptibility to osteonecrosis of the femoral head. [ 12 ] Familial osteonecrosis of the femoral head is typically inherited as an autosomal dominant trait, [ 13 ] and thus offspring are likely to have the same genetic mutation leading to the disease. Existing gene detection techniques can be used to provide molecular prenatal diagnosis along with further genetic counseling to enable early and effective interventions and treatments.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] To date, the knowledge on the development of LCPD in humans is limited because of the vast number of mutations found in the COL2A1 gene and the variability in the clinical phenotype. [41,42] It is apparent that the process in which mutations in collagens alter connective tissues is complicated and cannot be described by one single pathway. In the future study, this pedigree can be extended by including the distal relatives of the family, which we believe can probably shed some light into the delineation of the pathological phenotype heterogeneity of this disease.…”
Section: Discussionmentioning
confidence: 99%